Correction to: Impact on granular bed: validation of discrete element modeling results by means of two-dimensional finite element analysis (Granular Matter, (2020), 22, 1, (27), 10.1007/s10035-019-0988-1) - Marzulli, Valentina; Cisneros, Luis Armando Torres; Di Lernia, Annamaria; Windows-Yule, Christopher Robert Kit; Cafaro, Francesco; Pöschel, Thorsten (Granular Matter, 2021)
The article “Impact on granular bed: validation of discrete element modelling results by means of two-dimensional finite element analysis” written by Valentina Marzulli, Luis Armando Torres Cisneros, Annamaria di Lernia, Christopher Robert Kit Windows-Yule, Francesco Cafaro, Thorsten Pöschel was originally published Online First without Open Access. After publication in volume 22, issue 1, article 27 the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2020 and the article is forthwith distributed under the terms of the Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0. The original article has been corrected.
CRIS-Team Scopus Importer:2021-05-14

Erratum: Hydraulic Characterization of a Pervious Concrete for Deep Draining Trenches (J. Mater. Civ. Eng DOI: 10.1061/(ASCE)MT.1943-5533.0002274) - Marzulli, Valentina; Cafaro, Francesco; Ziccarelli, Maurizio (Journal of Materials in Civil Engineering, 2022)
The following correction should be made to the original paper. The symbols in the legend of Fig. 9 are inverted. The empty circle should refer to the drying process. (Figure Presented). To preserve the published version of record, these details have been corrected only in this erratum.
CRIS-Team Scopus Importer:2024-12-16

Geotechnical Properties of Uncompacted DNA-1A Lunar Simulant - Marzulli, Valentina; Cafaro, Francesco (Journal of Aerospace Engineering, 2019)
Understanding the mechanical behavior of lunar regolith is of great importance to address the building of structures on the Moon, as well as for predicting the response of some equipment or facilities interacting with the lunar soil (i.e., rovers). Because the number of lunar regolith samples on Earth is quite low due to the difficulties of bringing it back during space missions, in the last decades, researchers started to develop similar materials, usually named lunar regolith simulants. This paper reports the geotechnical characterization of the De NoArtri (DNA) lunar simulant carried out in the laboratory. Compositional analyses and mechanical tests have been carried out to characterize this simulant; particle-size distribution analysis, chemical analysis, and scanning electron microscope (SEM) analysis have been performed to identify the DNA-1A from a compositional point of view, as well as triaxial compression, direct shear, and oedometer tests for depicting its mechanical behavior, with some comparison with original lunar soil and other simulants.
CRIS-Team Scopus Importer:2019-12-03
Keywords: DNA simulant; Loose behavior; Lunar simulant; Lunar soil; Lunar structures; Moon

Impact in granular matter: Force at the base of a container made with one movable wall - Torres Cisneros, Luis Armando; Marzulli, Valentina; Windows-Yule, C. R. K.; Pöschel, Thorsten (Physical Review E, 2020)
In geotechnics as well as in planetary science, it is important to find a means by which to protect a base from impacts of micrometeoroids. In the moon, for example, covering a moon base with regolith, and housing such regolith by movable bounding walls, could work as a stress-leaking shield. Using a numerical model, by performing impacts on a granular material housed in a rectangular container made with one movable sidewall, it is found that such wall mobility serves as a good means for controlling the maximum force exerted at the container's base. We show that the force exerted at the container's base decreases as the movable wall decreases in mass, and it follows a Janssen-like trend. Moreover, by making use of a dynamically defined redirecting coefficient K (X), proposed by Windows-Yule et al. [Phys. Rev. E 100 , 022902 (2019)], which depends on the container's width X , we propose a model for predicting the maxima measured at the container's base. The model depends on the projectile and granulate properties, and the container's geometry.
CRIS-Team WoS Importer:2020-07-31

Impact on granular bed: validation of discrete element modeling results by means of two-dimensional finite element analysis - Marzulli, Valentina; Torres Cisneros, Luis Armando; di Lernia, Annamaria; Windows-Yule, Christopher Robert Kit; Cafaro, Francesco; Pöschel, Thorsten (Granular Matter, 2020)
The study of processes characterized by impulsive nature (i.e. impacts) can be considered of great interest in both physics and engineering disciplines: in the geotechnical field, for instance, their effect on the interaction between soil and structures need to be investigated. The present work aims at the validation, by means of two-dimensional finite element simulations, of a methodology of force calibration which uses results obtained from three-dimensional discrete element analysis for predicting the stress at the base of a granular bed, retained by a movable wall, arising when the system is hit by a projectile. To approach this problem, the low-velocity impact has been modeled as a punctual impulsive force on a granular packing.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Discrete element model; Finite element analysis; Granular material; Impact response; Numerical simulations; Soil–structure interaction

Janssen effect in dynamic particulate systems - Windows-Yule, C. R. K.; Mühlbauer, Sebastian; Torres Cisneros, Luis Armando; Nair, Prapanch; Marzulli, Valentina; Pöschel, Thorsten (Physical Review E, 2019)
The Janssen model of stress redistribution within laterally bounded particulate assemblies is a longstanding and valuable theoretical framework, widely used in the design of industrial systems. However, the model relies on the assumption of a static packing of particles and has never been tested in a truly dynamic regime nor for a constraining system whose geometry is dynamically altered. In this paper, we explore the pressure distributions of granular beds housed within a container possessing a laterally mobile sidewall, allowing the depth, height, and cross-sectional areas of the systems studied to be dynamically altered, thus, inducing particle rearrangements and flow in the particulate system constrained thereby. We demonstrate that the systems studied can be successfully described by the Janssen model across a wide range of system expansion rates, including those for which liquidlike flow is clearly observed and propose an extension to the model allowing for an improved characterization of constrained dynamic systems.
CRIS-Team WoS Importer:2019-09-06

Micromechanical Behavior of DNA-1A Lunar Regolith Simulant in Comparison to Ottawa Sand - Sandeep, C. S.; Marzulli, Valentina; Cafaro, F.; Senetakis, K.; Pöschel, Thorsten (Journal of Geophysical Research. Solid Earth, 2019)
In this study, the micromechanical interparticle contact behavior of “De NoArtri” (DNA-1A) grains is investigated, which is a lunar regolith simulant, using a custom-built micromechanical loading apparatus, and the results on the DNA-1A are compared with Ottawa sand which is a standard quartz soil. Material characterization is performed through several techniques. Based on microhardness intender and surface profiler analyses, it was found that the DNA-1A grains had lower values of hardness and higher values of surface roughness compared to Ottawa sand grains. In normal contact micromechanical tests, the results showed that the DNA-1A had softer behavior compared with Ottawa sand grains and that cumulative plastic displacements were observed for the DNA-1A simulant during cyclic compression, whereas for Ottawa sand grains elastic displacements were dominant in the cyclic sequences. In tangential contact micromechanical tests, it was shown that the interparticle friction values of DNA-1A were much greater than that of Ottawa sand grains, which was attributed to the softer contact response and greater roughness of the DNA-1A grains. Widely used theoretical models both in normal and tangential directions were fitted to the experimental data to obtain representative parameters, which can be useful as input in numerical analyses which use the discrete element method.
CRIS-Team Scopus Importer:2019-08-27
Keywords: interparticle friction; lunar regolith simulant; micromechanics; quartz sand

Scale and water effects on the friction angles of two granular soils with different roughness - Marzulli, Valentina; Sandeep, C. S.; Senetakis, K.; Cafaro, F.; Pöschel, Thorsten (Powder Technology, 2021)
An integrated experimental study is presented which aims at relating the frictional properties at the particle scale to the bulk mechanical behavior for two different types of sands. We performed direct shear tests and inter-particle tests on lunar regolith simulant DNA-1A and Ottawa sand (benchmark material) under both dry and wet conditions. We found higher macroscopic friction angles for the lunar simulant in both dry and wet conditions, a smaller strength decay for Ottawa sand during reversal direct shear tests and similar strength envelopes of both materials under wet and dry conditions. Particle-scale tests evidenced higher inter-particle friction for DNA-1A in wet conditions with respect to the dry case for normal force lower than 2–3 N. For the lunar simulant, the differences between bulk and inter-particle friction appeared to be emphasized in dry condition and an evident effect of water on the friction coefficient was found only at the micro-scale.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Granular material; Inter-particle friction; Lunar regolith simulant; Macroscopic friction angle; Ottawa sand; Roughness